Several Factors Contributing toward Flies Density at Fishing Port of Karangsong, Indramayu Regency - Marina Makbul; Martini Martini; Nur Endah Wahyuningsih (Postgraduate, University of Mataram, 2023)
Flies are mechanical vectors for several pathogens that can cause diarrhea. Fly density figures are used to assess environmental sanitation in a place. The aim of this study is to analyze the density of flies at the Karangsong Indramayu fish port. This study was conducted in July – August 2023. This study used an observational survey method with a cross sectional study design. Flies were caught using fly grills and traps and the catching area was divided into 3 zones. The variables analyzed were fly activity, temperature, humidity, wind speed, light intensity and fly density. There was a relationship between fly activity patterns in each zone and fly density (p< 0,05). There was a relationship between the environmental temperature of each zone (p< 0,05). There was a relationship between environmental humidity and fly density in each zone (p< 0,05). There was no relationship between wind speed and fly density for each zone (p> 0,05). There was a relationship between light intensity and fly density for each zone (p< 0,05). Factors contributing to the high density of flies at the Karangsong Indramayu Fish Port are fly activity patterns, temperature, humidity and light intensity